Effects of Sodium Iso-butyl Xanthate Dosage on The Froth Flotation of Bead Milled Middle Group 1-3 PGM Ore Blend - Nthapeleng M. Madilen; Abraham A. Adeleke; Peter Mendonidis (Graduate Program of Syiah Kuala University, 2015)
An investigation was carried out to determine the effects of collector concentration on the grade and recovery in the flotation of middle group 1-3 Platinum Group Metal (PGM) ore mixture. The ore mixture pulp at a relative density of 1.29 was subjected to “bead milling” test, particle size distribution analysis and the 55% passing 75 µm was froth floated at 180, 200 and 220 g/t dosages of sodium isobutyl xanthate (SIBX) and 30 and 80 g/t of Senfroth and Sendep 30D frother and depressant, respectively. The results obtained indicated the predominance of the 38 µm PGM values in the ore and confirmed the need for tertiary milling for better liberation of the PGMs. The grade of the PGM concentrate obtained when dosing at 200 g/t of sodium isobutyl xanthate was highest at 94 g/t and gave the lowest recovery of 53%. The 180 g/t SIBX dosage resulted in highest PGM recovery of 70% and lowest grade of 84 g/t, while dosing at 220 g/t SIBX gave average PGM grades of 90 g/t and recoveries of 60%. The results obtained thus showed that that an SIBX dosage of 180 g/t SIBX would be appropriate when higher recoveries are targeted, while 200 g/t dosage will yield higher grades